Mitochondrial Quality Control and Cellular Proteostasis: Two Sides of the Same Coin - Quiles, Justin M.; Gustafsson, Åsa B. (Frontiers in Physiology, 2020)
Mitochondrial dysfunction is a hallmark of cardiac pathophysiology. Defects in mitochondrial performance disrupt contractile function, overwhelm myocytes with reactive oxygen species (ROS) and transform these cellular powerhouses into pro-death organelles. Thus, quality control pathways aimed at identifying and removing damaged mitochondrial proteins, components or entire mitochondria are crucial processes in post-mitotic cells such as cardiac myocytes. Almost all of the mitochondrial proteins are encoded by the nuclear genome and the trafficking of these nuclear-encoded proteins necessitates significant cross-talk with cytosolic protein quality control machinery to ensure that only functional proteins are delivered to the mitochondria. Within the organelle, mitochondria contain their own protein quality control system consisting of chaperones and proteases. This system represents another level of quality control to promote mitochondrial protein folding and prevent aggregation. If this system is overwhelmed, a conserved transcriptional response known as the mitochondrial unfolded protein response is activated to increase the expression of proteins involved in restoring mitochondrial proteostasis. If the mitochondrion is beyond repair, the entire organelle must be removed before it becomes cytotoxic and causes cellular damage. Recent evidence has also uncovered mitochondria as participants in cytosolic protein quality control where misfolded cytosolic proteins can be imported and degraded inside mitochondria. However, this process also places increased pressure on mitochondrial quality control pathways to ensure that the imported proteins do not cause mitochondrial dysfunction. This review is focused on discussing the pathways involved in regulating mitochondrial quality control and their relationship to cellular proteostasis and mitochondrial health in the heart.